The Use of Sorption Clay Materials in Polymer Production Technologies - Sakalova, H. V.; Kryklyvyi, R. D.; Trach, I. A. (Visnyk of Vinnytsia Politechnical Institute, 2022)
The work is devoted to solving the urgent problem of increasing the level of environmental safety of wastewater treatment of industrial production from heavy metal ions through the use of natural and modified bentonite. Studies have been conducted to use spent bentonite in filling processes of polimers. The aim of the work was to study the influence of fillers on the cross linking course and functional properties of vulcanizates of elastomeric mixtures. Test compositions included chloroprene rubber and chlorosulfonated polyethylene. Nanofillers were used as a strengthening substance. Montmorillonite and spent montmorillonite saturated with cuprum ions used as nanofiller. The obtained values of bulk equilibrium swelling indicate that CR/SBR/Cu2O mixtures, which additionally contain copper ions in the filler, are more crosslinked and less swollen in toluene. According to the results of physical and mechanical tests and studies of polymers after thermal oxidative aging, it was determined that option 4 is closer in value to option 3 (used modified modified montmorillonite was used for filling). The variant of samples 4, containing spent bentonite in the amount of 5 ppm, received the highest value of the modulus of elasticity ΔG' = 1,971 MPa, ie has the most branched structure of the filler. All manufactured materials CR/SBR/Cu2O, belong to non-combustible materials, as evidenced by the values of the oxygen index, which exceed 30 %.